Strategic Principal Leadership in Educational Institution Development Planning - Miki Sandi; Akhmad Muaddin; Muchammad Eka Mahmud (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2026)
Educational institutions face complex challenges that demand effective leadership, yet school planning often remains a mere administrative compliance rather than a strategic improvement tool. This study aims to analyze the strategic role of principal leadership in the educational institution development planning process. Utilizing a systematic literature review with a thematic analysis approach, this research examined relevant peer-reviewed articles published between 2020 and 2026 sourced from major academic databases. The findings reveal four pivotal themes regarding effective planning leadership. First, successful principals shift towards data-driven planning and root-cause analysis integrated with local institutional values. Second, they implement distributed leadership to foster collaborative planning and cultivate teacher leadership. Third, effective development plans prioritize teacher professional development in their strategic programs and resource allocation, ensuring continuous knowledge transfer. Fourth, principals must exercise managerial flexibility through short-cycle planning to overcome bureaucratic constraints and administrative traps. Ultimately, the study concludes that principals must transcend their traditional administrative roles to act as strategic architects. By integrating data, distributing leadership, prioritizing teacher capacity, and maintaining agility, principals can transform rigid planning documents into dynamic catalysts for sustainable school improvement and educational excellence.